Regeneration of tooth and maxillofacial bone defects based on stem cell aggregates - FU Fei; HU Jiachen; SUI Bingdong; XUAN Kun; JIN Yan (Kouqiang hemian waike zazhi)
Dental and maxillofacial tissue defects represented by tooth defect and/or loss, and maxillofacial bone defect are very common in oral and maxillofacial patients. The current treatment methods include autologous or allogeneic tissue transplantation, artificial synthetic material simulation replacement, etc., which cannot achieve physiological dental and maxillofacial tissue structure and function repair. Mesenchymal stem cells (MSCs) have extensive and powerful potential in regenerative medicine application. Stem cell polymer technology based on the principle of mesenchymal condensation and development has the functional characteristics of maintaining cell stemness , remodeling regenerative microenvironment, and restarting histological differentiation. It has been successfully applied to the regeneration and repair of dental pulp, periodontal and bone tissue, which has obtained good efficacy in related clinical trials, and possess a better clinical transformation prospect. Good results have been obtained in relevant clinical trials, and it has a good prospect of clinical transformation. This review highlights the theoretical basis, construction method and research status of stem cell polymerization in dental tissue regeneration, so as to provide new clinical treatment ideas for better realization of the regeneration and repair of dental tissue defects.